Interferonopathies masquerading as non-Mendelian autoimmune diseases: pattern recognition for early diagnosis - Gagne, Samuel; Sivaraman, Vidya; Akoghlanian, Shoghik (Frontiers in Pediatrics, 2023)
Type I interferonopathies are a broad category of conditions associated with increased type I interferon gene expression and include monogenic autoinflammatory diseases and non-Mendelian autoimmune diseases such as dermatomyositis and systemic lupus erythematosus. While a wide range of clinical presentations among type I interferonopathies exists, these conditions often share several clinical manifestations and implications for treatment. Presenting symptoms may mimic non-Mendelian autoimmune diseases, including vasculitis and systemic lupus erythematosus, leading to delayed or missed diagnosis. This review aims to raise awareness about the varied presentations of monogenic interferonopathies to provide early recognition and appropriate treatment to prevent irreversible damage and improve quality of life and outcomes in this unique patient population.